2011
DOI: 10.1038/ni.2047
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine 1-phosphate receptor S1P2 maintains the homeostasis of germinal center B cells and promotes niche confinement

Abstract: Sphingosine-1-phosphate receptor-2 (S1P2)-deficient mice develop diffuse large B cell lymphoma. However, the role of S1P2 in normal germinal center (GC) physiology is unknown. Here we show that S1P2-deficient GC B cells outgrow their wild-type counterparts in chronically-established GCs. We find that S1P2-, G12–G13- and p115RhoGEF-mediated antagonism of Akt regulates cell viability and is required for growth control in chronically proliferating GCs. We also find that S1P2 inhibits GC B cell responses to follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
275
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(294 citation statements)
references
References 51 publications
12
275
0
Order By: Relevance
“…Physiologically, insulin-mediated glycogen synthesis is diminished in response to S1P, suggesting that the sphingolipid mediator may contribute to hepatic insulin resistance keratinocytes via stimulation of the S1P 2 receptor subtype [14]. This is in accordance with a variety of studies indicating that S1P 2 inhibits proliferation in several cells such as mouse embryonic fibroblasts and germinal centre B cells [36,37]. The present study provides evidence that S1P 2 stimulation is able to attenuate insulin-dependent Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Physiologically, insulin-mediated glycogen synthesis is diminished in response to S1P, suggesting that the sphingolipid mediator may contribute to hepatic insulin resistance keratinocytes via stimulation of the S1P 2 receptor subtype [14]. This is in accordance with a variety of studies indicating that S1P 2 inhibits proliferation in several cells such as mouse embryonic fibroblasts and germinal centre B cells [36,37]. The present study provides evidence that S1P 2 stimulation is able to attenuate insulin-dependent Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, an inhibitory effect of the S1P/S1P 2 axis on Akt activation has been identified, especially in immune cells. It has been suggested that, by inhibiting Akt activation, S1P 2 helps to restrict germinal centre B cell survival and localisation to an S1P-low niche at the follicle centre [37]. Moreover, S1P has been shown to inhibit the endocytotic capacity of dendritic cells by S1P 2 receptor activation and Akt inactivation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The sphingosine-1-phosphate receptor S1PR2 helps to confi ne B cells to the GC ( 37 ). GC B cells showed the highest gene expression of S1pr2 .…”
Section: Cd35mentioning
confidence: 99%
“…In the current study, we demonstrated that P. chabaudi is capable of inducing an increase in plasma cells at 17 dpi, and depletion of IFN-g resulted in significantly increased plasma cell percentages in both NP-OVA control and P. chabaudi-and NP-OVA-injected mice. At present, it is unclear whether malaria modulates signals important to either the organization of the GC such as CXCL13 (62,63) or lymphocyte migration signals involving sphingosine 1-phosphate (64) that are critical to the GC reaction. The lack of detectable NP + cells in GCs following NP-OVA injection of P. chabaudi-infected mice, but the presence of NP-specific Ab suggests that the response to NP-OVA is extrafollicular during P. chabaudi infection.…”
Section: Discussionmentioning
confidence: 99%